2015
DOI: 10.1002/hrm.21679
|View full text |Cite
|
Sign up to set email alerts
|

Age and Assessments of Disability Accommodation Request Normative Appropriateness

Abstract: In the United States, the labor force continues to age. As age increases, so does the likeliness of needing disability accommodation. Prior research indicates that people with disabilities often do not request needed accommodations when they assess that others at work would perceive a request as normatively inappropriate. Little, however, is currently known about the impact of age on these assessments. In this study, we integrate prior research on age, disability, social identity, and climate to propose and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 38 publications
0
28
0
2
Order By: Relevance
“…For example, Baldridge and Veiga () investigated how persons with hearing disabilities decide to request accommodations based on their assessment of the likelihood of compliance, normative beliefs, and anticipated psychosocial consequences, with greater monetary costs and impositions on others negatively influencing these assessments. Baldridge and Swift (, ) extended this research by examining the interaction between employee attributes (age, gender, disability severity, and onset age), organizational/workplace characteristics (having coworkers with disabilities, for‐profit organization context), and psychological assessments and behavioral responses of the employee with a disability. Similarly, Dong, Fabian, and Xu () found individuals' self‐efficacy, outcome expectancy, and positive affect increase the willingness of employees with disabilities to request accommodation.…”
Section: Review Of Empirically Investigated Relationshipsmentioning
confidence: 99%
“…For example, Baldridge and Veiga () investigated how persons with hearing disabilities decide to request accommodations based on their assessment of the likelihood of compliance, normative beliefs, and anticipated psychosocial consequences, with greater monetary costs and impositions on others negatively influencing these assessments. Baldridge and Swift (, ) extended this research by examining the interaction between employee attributes (age, gender, disability severity, and onset age), organizational/workplace characteristics (having coworkers with disabilities, for‐profit organization context), and psychological assessments and behavioral responses of the employee with a disability. Similarly, Dong, Fabian, and Xu () found individuals' self‐efficacy, outcome expectancy, and positive affect increase the willingness of employees with disabilities to request accommodation.…”
Section: Review Of Empirically Investigated Relationshipsmentioning
confidence: 99%
“…However, there has been surprisingly little research from the perspective of the primary actors in the accommodation process, i.e., employees with disabilities themselves (Balser and Harris, 2008 ). As one important exception, Baldridge and colleagues (Baldridge and Veiga, 2001 , 2006 ; Baldridge and Swift, 2013 , 2015 ) as well as Davison et al ( 2009 ) considered the perspective of employees with disabilities and systematically examined their tendency to request accommodations. Specifically, these studies focused on identifying factors that prevent employees with disabilities from requesting future job accommodations.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Baldridge and Swift (2016) suggested human resource professionals and management are essential for fostering work environments that are supportive and encourage understanding amongst co-workers. Similarly, Miceli et al (2002) suggested that a key intervention strategy is disability sensitisation workshops, the purpose being to increase awareness relating to disability, alter attitudes towards disability, overcome communication barriers and equip employers with the necessary skills and tools to do so.…”
Section: Discussionmentioning
confidence: 99%